Corporate cash holding: an empirical investigation of public listed companies for trading/service sector in Malaysia - Rubadharishini, Chelliah (2017)
This study investigates the empirical investigation between corporate cash holdings as the dependent variable and firm size, cash flow volatility, leverage and capital expenditure as independent variable by taking Malaysia trading/service sector of public listed companies as the sample over the period from 2014 to 2016. This study applied tradeoff and pecking order theory in order to show briefly on corporate cash holdings level. Descriptive analysis and hypothesis analysis are employed to analyze the relationship between those variables. The findings of this study reveal that firm size and leverage are negatively correlated to corporate cash holdings while cash flow volatility and capital expenditure highlights positive relationship to corporate cash holdings as for both tradeoff and pecking order theory. The excess cash holdings are a sign that the firm tends to retain the cash rather than pay it via dividends and there is a possibility that the cash is employed for non-pecuniary benefits which is not analogous to the shareholders' interest. The negative relationship shown by firm size might suggest that larger the firm size enables a firm to gather retain earnings where precisely debt is not important. For leverage, the negative relationship might indicate that corporations having ability to issue new debts holds less cash and used to fund new investments. The positive relationship is exhibited by cash flow volatility and capital expenditure. Companies fail to finance all profitable projects and faces larger cost of external financing where company can be short of liquid asset as suggested by both theories. Companies with high capital expenditure will face high amount of cash due to high cost in capital market reflects financial distress.